Treatment results of Hodgkin’s lymphoma in children and adolescents: data of a monocenter study - R. I. Feoktistov; J. V. Rumyantseva; Yu. G. Abugova; Yu. Yu. Dyakonova; O. V. Makarova; N. V. Myakova; E. V. Samochatova (Онкогематология)
Treatment results of children and adolescents with Hodgkin’s lymphoma (HL) treated at the Russian Children Clinical Hospital (Moscow) was described. 47 children and adolescents with HL were treated by modified DAL-HD-90 protocol. 45 (95.74 %) patients achieved remission. With a median follow-up time of 57.6 month 6-years overall, event-free and relapse-free survival were 95 ± 3, 91 ± 4 and 95 ± 3 %, respectively. The age 14 years and older and the 2 type nodular sclerosis of Hodgkin’s lymphoma were the poor prognostic factors.